Investigation of the relationship between modified Glasgow prognostic score and no-reflow phenomenon in patients undergoing primary percutaneous coronary intervention for ST-elevation myocardial infarction - Kaplangoray, Mustafa; Toprak, Kenan; Aydın, Cihan; Aslan, Ramazan (The European Research Journal, 2023)
Objectives: No-reflow phenomenon (NRP) is a complication associated with poor clinical outcome in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (pPCI). The modified Glasgow prognostic score (mGPS) is a novel immune-inflammatory index, derived from C-reactive protein (CRP) and serum albumin levels and has been shown to be associated with prognosis in heart disease. In this study we aimed to investigated the relationship between mGPS and NRP in patients undergoing pPCI for STEMI. Methods: A total of 379 patients (aged 59 ± 9.9 years; 54.9% male) were enrollled. The patients were divided into 2 groups:no-reflow (n = 72) and reflow (n = 307). No-reflow was defined as thrombolysis in myocardial infarction (TIMI) ≤ 2 flow. The mGPS of all patients was calculated from blood samples at admission. Logistic regression analysis was performed to determine the independent predictive factors for NRP. Results: Mean age, pain to balloon duration, troponin T, white blood cell (WBC), Syntax score, neutrophil to lymphocyte ratio (NLR), glucose level, C-reactive protein level (CRP), diabetic and female patient ratio were higher, while left ventricular ejection fraction, ST segment resolution ratio at 60 min, and serum albumin level were lower in the NRP group.Logistic regression analysis showed that WBC count [Hazard ratio (HR): 0.816, 95% confidence interval (CI): 0.728-0.914, p < 0.001], NLR (HR: 0.482, CI: 0.355-0.654, p < 0.001), pain-to-balloon time (HR: 0.976, CI:0.960-0.991, p = 0.002) and mGPS (HR: 3.213, CI: 1.643- 6.283, p = 0.001) were independent predictive factors for NRP. Conclusions: Modified GPS is an independent predictive factor for NRP in patients undergoing pPCI for STEMI.